Proteomics and glycoproteomics of beer and wine. Issue 15 (26th June 2022) - Liu, Shulei; Kerr, Edward D.; Pegg, Cassandra L.; Schulz, Benjamin L.
Abstract: Beer and wine are fermented beverages that contain abundant proteins released from barley or grapes, and secreted from yeast. These proteins are associated with many quality attributes including turbidity, foamability, effervescence, flavour and colour. Many grape proteins and secreted yeast proteins are glycosylated, and barley proteins can be glycated under the high temperatures in the beer making process. The emergence of high‐resolution mass spectrometry has allowed proteomic and glycoproteomic analyses of these complex mixtures of proteins towards understanding their role in determining beer and wine attributes. In this review, we summarise recent studies of proteomic and glycoproteomic analyses of beer and wine including their strategies for mass spectrometry (MS)‐based identification, quantification and characterisation of the glyco/proteomes of fermented beverages to control product quality.